Public Issues as Controversial Issues. History and Education Teachers approaching National Independence and Civic Education in the Chilean Bicentennial - Cavieres-Fernandez, Eduardo; Uzcátegui-Pacheco, Ramón Alexander (Revista Electrónica Educare, 2021)
Objective: This study aims to explore the public issues that Chilean high-school history teachers consider relevant to be discussed during the teaching of the national independence (1810-1818) for their students’ citizenship education in the context of the Chilean Bicentennial. Method: For this purpose, qualitative instruments, such as interviews and classroom observations, are conducted with main participants and group interviews with secondary participants from four cities throughout the country. Results: These teachers coincide in pointing out problems concerning power relations that affect the public sphere, before which the teaching of the national independence provides elements for in-depth reflections on these issues. Conclusions: Although there were no discussions around these problems in the classes observed with the teachers, the exchanges initiated by the teachers around these topics should be valued, at least, as an attempt to make them controversial in curricular contexts that do not always allow for discussion.